Effects of active site residues of 3α-hydroxysteroid dehydrogenase from pseudomonas sp. b-0831 on its catalysis and cofactor binding. Issue 10 (3rd October 2018) - Shiota, Ayako; Inaba, Satomi; Oda, Masayuki
ABSTRACT: We overexpressed and purified 3α-hydroxysteroid dehydrogenase from Pseudomonas sp. B-0831 (Ps3αHSD) and its mutants where the active site residues known as the SYK triad, Ser114, Tyr153, and Lys157, were mutated. Ps3αHSD catalyzes the reaction by using a nucleotide cofactor. The NADH binding affinity of K157A mutant was much lower than that of the wild-type, mainly due to loss of a hydrogen bond. The decreased affinity would result in decreased k cat. Compared to the wild-type, the mutants S114A and Y153F showed higher K m and lower k cat values in both oxidation and reduction reactions. Simultaneous mutation of S114A and Y153F resulted in a significant decrease in k cat relative to the single mutant. These results are supported by the notion that Tyr153 is a catalytic base and Ser114 would be a substitute. Loss of hydrogen bonding with NADH upon the Y153F mutation resulted in increased enthalpy change, partially compensated by increased entropy change. Graphical abstract: : Crystal structure of Ps3aHSD and ITC profile for NADH binding. The effects of mutations on catalysis and cofactor binding are well correlated with the structural information.